Perceived Security and Trust in Electronic Payment Systems: How They Affect the Decision to Use EPS During the COVID-19 Pandemic - Primadineska, Rasistia Wisandianing; Jannah, Syayyidah Maftuhatul (Jurnal Manajemen Bisnis, 2021)
Research aims: This study is intended to determine the influence of perceived security and trust on the decision to use digital payment systems during the COVID-19 pandemic.Design/Methodology/Approach: The type of data used in this study was primary data, which was collected using an online survey. Sample used in this study determined by purposive sampling method. The information collected was handled and analyzed using SEM-PLS.Research findings: This study shows the results that the presence of technical protection explicitly affects the perception of security and trust significantly. In addition, security also greatly affects an individual's confidence in the use of digital payment systems. However, of the various findings made in this study, trust is the only one that influences the choice in using EPS.Theoretical contribution/Originality: During this pandemic Covid-19, limited studies talk about consumers’ perceptions instead of technical protection of digital payment in detail. Meanwhile, consumers' security is the thing that needs to be studied further to create a comprehensive study result.Practitioner/Policy implication: Results of this study give some implications for the EPS providers to complete and develop a secure EPS system for users, especially in this pandemic era when the EPS users increase and people’s mobility is restricted in some areas.Research limitation/Implication: The implication of this research is to emphasize the importance of one's knowledge regarding risks when using an electronic payment system. It is because the use of EPS in the pandemic era is unavoidable. Therefore, not only providers must improve their security systems, but users must also be aware of the EPS risks and security. Nevertheless, the limitation of this study is that it only used samples in Indonesia; maybe the results will be different when applied in other countries with better EPS security systems.